Visual thinking puzzles - Dispezio, Michael A. (New York : Sterling Pub. Co., 1998)
Presents more than sixty puzzles that develop mental skills using patterns, grids, and pictures, with explained answers.
Includes index.
Adult
Keywords: Puzzles; Visual perception; Puzzles; Visual perception